Diethylaminoethyl octanoate citrate alleviates low temperature stress in wheat seedlings by modulating antioxidative responses - Wang, Guoquan; Lu, Panpan; Wang, Yanyan; Zhu, Yifan; Li, Jingfeng; Fei, Liwei; Xu, Li; Zhang, Ying; Li, Weiguo; Zhou, Feng; Liu, Runqiang (Plant physiology and biochemistry, 2025)
Low temperature stress (LTS) is a common abiotic stress that can seriously hinder the growth and development of wheat plants, and which in severe cases may result in crop failure and threaten local food security. The current study used a hydroponic approach to explore the effect of the plant growth regulator (PGR) diethylaminoethyl octanoate citrate (DA-8 citrate) on the morphological and physiological characteristics, as well as key stress markers in wheat seedlings exposed to LTS. The results reconfirmed the growth promoting effects of DA-8 citrate in the absence of stress (25 °C/20 °C day/night), and found that seed-treatment with DA-8 citrate was able to alleviate the growth inhibition resulting from LTS (2 °C/0 °C day/night), and even promote root growth at the optimal concentration of 30 mg.L−1. The treated seedlings were found to have elevated levels of chlorophyll, which likely contributed to their enhanced growth. Meanwhile, treatment with DA-8 citrate was also found to mitigate osmotic stress and reduce oxidative damage resulting from exposure to low temperature, as the optimal dose promoted the accumulation of soluble proline and sugar to combat osmotic stress, and reduced the accumulation of malondialdehyde (MDA), a key marker for lipid peroxidation and oxidative damage, to levels similar to those observed in plants not subject to LTS. Furthermore, it was also noted that the activity of antioxidative enzymes including superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX) was increased in the seedling treated with the optimal dose of DA-8 citrate, which was likely the cause of the reduced MDA content of their leaves. Taken together, these results indicate that DA-8 citrate has great potential as a PGR that can alleviate the symptoms of LTS in wheat, not only promoting growth via elevated chlorophyll levels, but also by increasing resilience to osmotic and oxidative stress. [Display omitted] •Seed pretreatment with DA-8 citrate offers a promising strategy to enhance low temperature resilience in wheat.•DA-8 citrate can activate antioxidant enzyme activity and improve ROS scavenging efficiency.•DA-8 citrate can promote the accumulation of osmoprotective substances and improve osmoregulation under LTS.